1977
DOI: 10.1530/jrf.0.0500103
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an inhibitory influence of oocytes upon luteinization of porcine granulosa cells in culture

Abstract: Nalbandov (1972) suggested that the ovum produces a "luteostatic" substance which prevents luteinization of granulosa cells. This suggestion was derived from three lines of observation: (1) surgical ovectomy in vivo induced luteinization and increased the output of progesterone into the ovarian venous blood of rabbits (El-Fouly, Cook, Nekola & Nalbandov, 1970) and pigs (Nalbandov, 1972); (2) rat granulosa cell monolayers cultured with only a few oocytes luteinized, whereas those cultured in the presence of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The resumption of oocyte meiosis may not only depend on active stimulation. This process may also involve a removal of inhibitory signals, as previously proposed (Channing and Tsafriri, 1977;Channing et al, 1983). A change in the balance between inhibitory and stimulatory substances of the follicle fluid might be involved in the resumption of meiosis (Westergaard et al, 1984;review, Byskov, 1979).…”
Section: Discussionmentioning
confidence: 79%
“…The resumption of oocyte meiosis may not only depend on active stimulation. This process may also involve a removal of inhibitory signals, as previously proposed (Channing and Tsafriri, 1977;Channing et al, 1983). A change in the balance between inhibitory and stimulatory substances of the follicle fluid might be involved in the resumption of meiosis (Westergaard et al, 1984;review, Byskov, 1979).…”
Section: Discussionmentioning
confidence: 79%
“…Further studies in rats found that the addition of oocytes to granulosa cell cultures prevented morphological luteinization [14] and that luteinization of rat follicles in vitro [15] or in vivo [16] coincided with degeneration of the oocyte. Others have failed to observe any inhibitory influence of oocytes upon morphological luteinization or progesterone secretion [17][18][19]. By means of a microsurgical procedure, whereby the oocyte is removed from the oocyte-cumulus cell complex, it was shown that these oocytectomized (OOX) complexes produced 29% less estradiol, but almost 40-fold more progesterone, than did intact oocyte-cumulus cell complexes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies in rats found that addition of oocytes to granulosa cell cultures prevented morphological luteinisation (Nekola & Nalbandov, 1971), and that luteinisation of rat follicles in vitro (Stoklosowa & Nalbandov, 1972) or in vivo (Hubbard & Erickson, 1988) coincided with degeneration of oocytes. Others have failed to observe any inhibitory influence of oocytes upon morphological luteinisation or progesterone secretion (Nicosia, 1972;Lindner et ah, 1974;Charming & Tsafriri, 1977). It should be noted, however, that the ability for the oocyte to regulate the follicular environment is not limited to mammals, as destruction of the germinal disc region of chicken ovaries prevents the preovulatory rise in progesterone and blocks ovulation (Yoshimura e t ah, 1994), and Xenopus oocytes seem to influence the steroid synthetic pattern of the surrounding follicle cells (Wallace, 1983).…”
mentioning
confidence: 99%